2009
DOI: 10.1254/jphs.08284fp
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Synthetic Sphingosine-1-Phosphate Analogs on Cytosolic Phospholipase A2α–Independent Release of Arachidonic Acid and Cell Toxicity in L929 Fibrosarcoma Cells: the Structure–Activity Relationship

Abstract: Abstract. Sphingolipid metabolites including ceramide, sphingosine, and their phosphorylated products [sphingosine-1-phosphate (S1P) and ceramide-1-phosphate] regulate cell functions including arachidonic acid (AA) metabolism and cell death. The development of analogs of S1P may be useful for regulating these mediator-induced cellular responses. We synthesized new analogs of S1P and examined their effects on the release of AA and cell death in L929 mouse fibrosarcoma cells. Among the analogs tested, several co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…AA and its metabolites have been established to show cytotoxicity and be involved in various diseases such as neurological disorders and liver and myocardial injuries [Farooqui et al, ; Yagami et al, ]. Previously, we reported that exogenously added AA and AA released endogenously by Ca 2+ ‐dependent cytosolic PLA 2 and by other PLA 2 s caused cell death in L929 fibrosarcoma cells [Kurosawa et al, ; Shimizu et al, ] and CHO cells [Nakamura et al, ]. Several sPLA 2 such as human sPLA 2 ‐IB and ‐IIA, and sPLA 2 ‐III from bee venom have been shown to cause cell death including apoptosis in neuronal cells [Yagami et al, , ; DeCoster, ].…”
Section: Introductionmentioning
confidence: 99%
“…AA and its metabolites have been established to show cytotoxicity and be involved in various diseases such as neurological disorders and liver and myocardial injuries [Farooqui et al, ; Yagami et al, ]. Previously, we reported that exogenously added AA and AA released endogenously by Ca 2+ ‐dependent cytosolic PLA 2 and by other PLA 2 s caused cell death in L929 fibrosarcoma cells [Kurosawa et al, ; Shimizu et al, ] and CHO cells [Nakamura et al, ]. Several sPLA 2 such as human sPLA 2 ‐IB and ‐IIA, and sPLA 2 ‐III from bee venom have been shown to cause cell death including apoptosis in neuronal cells [Yagami et al, , ; DeCoster, ].…”
Section: Introductionmentioning
confidence: 99%